ANALISIS PENYEBAB PRODUK NOT GOOD PACKING COUMPOUND DENGAN METODE SIX SIGMA DMAIC DI PT. A&A - Akhsani Nur Amalia; Anisa Agustina (Sekolah Tinggi Teknologi Wastukancana, 2024)
Research was conducted to determine the factors that cause the occurrence of not good products in Packing Compound. The research was conducted in the Quality Control department of PT A&A. The analysis was conducted using the Six Sigma DMAIC method. Pareto diagram shows that there are four types of not good that need immediate improvement, namely not good torn, dirty, short mold and visual. Cause analysis was conducted using Failure Mode and Effect Analysis (FMEA). The analysis results prove that human factors, materials, machines and methods are the factors that cause the occurrence of not good products. Therefore, the company needs to increase the number of skilled workers, implement SOPs properly and conduct scheduled machine checks and maintenance. Keywords: Quality, Six Sigma, DMAIC